2010
DOI: 10.1016/j.yjmcc.2010.08.008
|View full text |Cite
|
Sign up to set email alerts
|

ROCK1 plays an essential role in the transition from cardiac hypertrophy to failure in mice

Abstract: Pathological cardiac hypertrophy caused by diverse etiologies eventually leads to cardiac dilation and functional decompensation. We have recently reported that genetic deletion of Rho-associated coiled-coil containing protein kinase 1 (ROCK1) inhibited several pathological events including cardiomyocyte apoptosis in compensated hypertrophic hearts. The present study investigated whether ROCK1 deficiency can prevent the transition from hypertrophy to heart failure. Transgenic mice with cardiac-restricted overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
98
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(106 citation statements)
references
References 29 publications
(55 reference statements)
8
98
0
Order By: Relevance
“…In contrast, although it does not prevent the development of cardiac hypertrophy, deletion of Rock1 improves survival, inhibits cardiomyocytes apoptosis, and preserves left ventricular structure and function in old G␣ q mice (442,443).…”
Section: Rho Proteinsmentioning
confidence: 94%
See 2 more Smart Citations
“…In contrast, although it does not prevent the development of cardiac hypertrophy, deletion of Rock1 improves survival, inhibits cardiomyocytes apoptosis, and preserves left ventricular structure and function in old G␣ q mice (442,443).…”
Section: Rho Proteinsmentioning
confidence: 94%
“…The resulting repression of the PI 3-kinase/Akt cell survival pathway thus sets on a positive feed-forward regulatory loop that favors cardiomyocyte apoptosis (72). Because cardiomyocyte apoptosis is a major cellular event involved in the transition from compensated hypertrophy to dilated cardiomyopathy and failure, this mechanism can support the observed important role of Rock1 in hypertrophic decompensation (443).…”
Section: Rho Proteinsmentioning
confidence: 97%
See 1 more Smart Citation
“…Chronic treatment with ROCK inhibitors limits agonist-or myocardial infarction-induced pathologic cardiac remodeling and hypertrophy in mice, suggesting a role of ROCKs in these processes (Kobayashi et al, 2002;Higashi et al, 2003;Satoh et al, 2003;Hattori et al, 2004;Wang et al, 2005;Loirand et al, 2013). The cardioprotective effects of ROCK inhibitors have been attributed to a reduction of cardiomyocyte hypertrophy induced by increased mechanical strains or soluble hypertrophic signals (Hoshijima et al, 1998;Yanazume et al, 2002;Brown et al, 2006), limitation of fibrosis (Li et al, 2012a;Yang et al, 2012), and inhibition of cardiomyocyte apoptosis Shi et al, 2010) Although the mechanisms underlying the involvement of ROCK1 and/or ROCK2 and their respective roles in cardiac hypertrophy have not been completely elucidated, an increase in cardiac ROCK1 activity has been detected in response to pressure overload (Zhang et al, 2006). The subsequent effect of ROCK activation may be related to the stimulation of hypertrophic gene transcription (Kuwahara et al, 2010), downregulation of endothelial nitric oxide synthase (eNOS), and an increase in oxidative stress (Kobayashi et al, 2002;Mita et al, 2005).…”
mentioning
confidence: 99%
“…Rho kinase 1 deletion did not impair compensatory hypertrophic response but significantly reduced cardiomyocyte apoptosis and fibrosis in response to pressure overload induced by transverse aortic constriction [24]. Another recent study showed the long-term beneficial effects of ROCK1 deficiency in hypertrophic decompensation and suggested that ROCK1 may be an attractive therapeutic target to limit heart failure progression [25]. In this study, the coronary angiography results showed that the coronary triple-vessel and left main lesion were more frequent in the DM group, but the Gensini score was similar between groups and the ROCK1 activity did not correlate with the Gensini score.…”
Section: Increased Rock1 Activity In Stemi Patients With Dmmentioning
confidence: 99%